Bovine brucellosis in relation to public health - Vinod VK (Department of Veterinary Public Health, College of Veterinary and Animal Sciences, 1999)
A serological survey was undertaken to assess the extent of brucellosis in bovines and humans. Serum samples from 1233 bovines and 747 human were collected. These samples were screened by Rose Bengal Plate Test (RBPT) and Standard Tube Agglutination Test (STAT). The samples which showed a positive reaction, either by RBPT or STAT or both were subjected to Heat inactivation test (HIT), 2- Mercaptoethanol test (MET) and EDTA agglutination test (EAT). Of the 610 slaughtered male bovine serum samples screened, 41 (6.72 per cent) was found positive by RBPT and 37 (6.07 per cent) by STAT. HIT, MET and EAT detected positive reaction in 32 (5.25 per cent), 26 (4.26 per cent) and 27 (4.43 per cent) samples respectively. A total of 23 samples were positive by all the above tests. Among the 518 slaughtered female bovine serum samples, RBPT detected 41 (7.92 per cent) samples as positive while only 38 (7.34 per cent) samples were found positive by STAT. HIT, MET and EAT detected positive reaction in 31 (5.98 per cent), 26 (5.02 per cent) and 28 (5.4 per cent) samples respectively. Twenty four serum samples were found positive for the disease by all the above tests. None of the serological test employed could detect a statistically significant difference in the seroprevalence of disease between males and females. Of the serum samples collected from 105 farm fed cows, six (5.7 per cent) samples were found positive for brucellosis by both RBPT and STAT. The number of samples found positive by HIT, MET and EAT were three (2.86 per cent), one